STUDI META-ANALISIS PENGARUH MODEL PROBLEM BASED LEARNING (PBL) DAN MODEL PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR SISWA - Sri Mulyati, - (2022)
Abstract This research aims to look at the impact of Problem Based Learning models and Project-Based Learning models on student learning outcomes and analyze the influence of Problem Based Learning models and Project-Based Learning models on high school / vocational student learning outcomes on Economics subjects. The research method used is a meta-analysis of scientific research articles published in a repository and national e-journals that apply problem-based learning models and Project-Based Learning models. The findings revealed that overall the studies conducted affected students' learning outcomes judging by the results of the problem-size problem-based learning model, project-based learning model, and standard deviation both in the category of large effects. Effect size and standard deviation of Problem Based Learning models from vocational and high school education levels have a major effect. Effect size and standard deviation model Project Based Learning vocational education level gives a moderate effect and high school education level has a big effect. This study concludes that the influence of problem-based learning models and project-based learning models is more effective in improving student learning outcomes in economics subjects compared to other learning models from this study at the high school and vocational high school levels. Keywords: Problem Based Learning Model, Project Based Learning Model, the meta analysis technique, the effect size, the achievement of students.